En affaldsbunke fra en pottemager i Åle: Præsentation af tendenserne i et keramikmateriale - Birkals, Asmund (Hikuin, 2001)
A waster from a potters’ workshop in Åle. A presentation of the tendencies in the pottery forms By Asmund Birkals A large find of pottery was made in 1955 in the central part of Jutland. In the town of Åle about 400 kilos of pottery were unearthed in an area that constituted about 36 m2. The circumstances of the find are described very superficially and there is no archaeological drawing of the construction. In order to form a general idea of this large quantity of pottery, about 40 kilos were examined to infer, if possible, the main tendencies in the composition of the pottery. The examination of the potsherds, which are highly fragmented, indicated that the find primarily consists of discarded vessels from a workshop that technically speaking produced rather primitive pottery. Only a limited part (3%) is glazed and the variation in form is quite limited. The majority of the potsherds are from cooking pots, while a smaller portion comes from jugs with handles. A closer examination of the excavator’s description opens the possibility that the burned red layers of clay in the ground under the site of the find are an indication of a potter’s kiln, but since the kiln construction was known in Denmark for the first time in 1955 this clue was possibly overlooked.